2008
DOI: 10.1002/bem.20404
|View full text |Cite
|
Sign up to set email alerts
|

Setup and dosimetry for exposing anaesthetised pigs in vivo to 900 MHz GSM mobile phone fields

Abstract: The aim of this study was a dosimetrical analysis of the setup used in the exposure of the heads of domestic pigs to GSM-modulated radio frequency electromagnetic fields (RF-EMF) at 900 MHz. The heads of pigs were irradiated with a half wave dipole using three different exposure routines; short bursts of 1-3 s at two different exposure levels and a continuous 10-min exposure. The electroencephalogram (EEG) was registered continuously during the exposures to search for RF-EMF originated changes. The dosimetry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The possible contamination of EEG signals due to direct pickup of mobile phone signals has often been discussed as a possible artifact in both human and animal EEG studies. However, no significant interferences were observed in EEG, especially for the physiologically important frequency range of 0.5-30 Hz [Wood et al, 2003;Toivonen et al, 2008].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The possible contamination of EEG signals due to direct pickup of mobile phone signals has often been discussed as a possible artifact in both human and animal EEG studies. However, no significant interferences were observed in EEG, especially for the physiologically important frequency range of 0.5-30 Hz [Wood et al, 2003;Toivonen et al, 2008].…”
Section: Discussionmentioning
confidence: 84%
“…The averaged response to the standard was subtracted from that to each deviant in order to delineate the MMN, resulting in four different waveforms, one for each deviant type. There was no direct coupling between EEG (1-30 Hz) and 900-MHz GSM signals [Wood et al, 2003;Toivonen et al, 2008].…”
Section: Methodsmentioning
confidence: 96%
“…Baseline correction was performed using a time window of À100 to 0 ms. Epochs, including EEG or EOG voltage exceeding AE75 mV and those for the first five standards of each stimulus sequence, were omitted from the averaging. There was no direct coupling between EEG (1-30 Hz) and 902 MHz GSM signals [Wood et al, 2003;Toivonen et al, 2008].…”
Section: Data Acquisitionmentioning
confidence: 96%
“…53 The body of the adult reference deer is roughly represented by an ellipsoid with dimensions of 50,52,65 A voxel-based frog model was also developed using cryosection images. 51 Toivonen et al 54 and Wake et al, 55 developed voxelbased pig and rabbit models, respectively, for finite-difference time-domain (FDTD) simulation of radio frequency (RF) radiation dosimetry. The University of Florida constructed a stylized model, a voxel model, and a hybrid model of the same 24 kg Hound cross canine specimen.…”
Section: C Computational Models Of Other Animalsmentioning
confidence: 99%
“…Following this study, animal SAR values were calculated and reported for mouse, rat, rabbit, and pig under RF exposures of 800 MHz-2 GHz cellular phone electromagnetic fields. 22,36,44,54,[113][114][115][116][117][118][119][120][121][122][123] Dosimetry calculations were performed for the exposure of mice and rabbit to 2.45 GHz WiFi frequencies. [124][125][126][127][128][129] Fig.…”
Section: B Nonionizing Radiation Dosimetrymentioning
confidence: 99%